Peran Literasi Keuangan dalam Menunjang Kinerja UKM: Sebuah Tinjauan Literatur Sistematis - Yunarni, Baiq Reinelda Tri; Mariadi, Yusli; Fadah, Isti (Universitas Hamzanwadi, 2025)
This research presents a systematic literature review, including content and bibliometric analysis, regarding the role of financial literacy in supporting the performance of small and medium enterprises (SMEs). The systematic literature review approach applied found 23 articles that were highly relevant to the role of financial literacy as a determining factor in SME performance. This study combines previous research findings regarding financial literacy over the last 5 years which plays a role in three forms of performance: (1) financial performance; (2) competitive advantage; and (3) sustainability performance. The findings of this research have the potential to have important impacts for SMEs, SME partners, governments and policy makers. By highlighting the lack of financial literacy among SMEs, this study provides a context for understanding the importance of financial literacy for SMEs. This study identified many areas of research that had not been explored previously